Anticancer Activity from Active Fraction of Sea Cucumber - Nurul Mutia Putram; Iriani Setyaningsih; Kustiariyah Tarman (Department of Aquatic Product Technology IPB University in collaboration with Masyarakat Pengolahan Hasil Perikanan Indonesia (MPHPI), 2017)
Sea Cucumber Holothuria atra is one of marine organisms has been used as a new source of novel bioactive compounds. Many of them have been used as the lead compounds in discovery of new anticancer drugs. The objective of this study was to determine the active fractions of sea cucumber (H. atra) which have anticancer activity. H. atra was macerated using ethanol and the extract was freezedried using a freeze dryer. The crude extract was partitioned using n-hexane, ethyl acetate, and methanol-water (3:1:1:1). Cytotoxicity test was performed using HeLa (cervic cancer) cell line and MCF-7 (breast cancer) cell line based on the MTT assay. The crude extract of H. atra showed the best cytotoxic activity against HeLa cells (IC50 = 12.48 µg/mL) and MCF-7 cells (IC50 = 17.90 µg/mL). The toxicity tests showed the IC50 value of the n-hexane fraction, ethyl acetate fraction, and methanol-water fraction against HeLa cells HeLa (IC50 = 76.45 µg/mL; 77.95 µg/mL; 14.27 µg/mL) and MCF-7 cells (IC50 = 58.50 µg/mL; 59.59 µg/mL; 14.33 µg/mL).